LATE ANTIQUE AND BYZANTINE POTTERY OF THE CHURCH OF ST. MARY IN EPHESOS. AN INTRODUCTION - Turnovsky, Petra (Rei Cretariae Romanae Fautorum Acta, 2024)
The city of Ephesos, situated on the western coast of Asia Minor opposite of the island of Samos, was an important religious center because of the famous temple of Artemis, a political center being the capital of the Roman province of Asia Minor and a center of trade and economy because of its port. The main part of the imported ceramics originated from the coastal area of the Mediterranean. There is substantial evidence for local productions, such as amphoras of the type Peacock – Williams class 45 and imitations of LRC ware.